Yield stability in coriander (Coriandrum sativum L.) - S K Nair, C R Gupta, N S Tomar, P Singh (Journal of Spices and Aromatic Crops, 2004)
The yield stability of eight elite accessions of coriander (Coriandrum sativum) was estimated under Chattisgarh plains condition at Raigarh (Chattisgarh). The accession JCO-387 yielded the highest, exhibiting above average response but unstable reaction (high S’di) while UD-744, DH-246 and UD-743 were promising and suitable for favourable environment.